P-EGS20 Safe emergency laparoscopic cholecystectomy in the first 12 months of the Covid-19 pandemic. (16th December 2021) - Michel, Martin; Fifer, Helen; Moran, Emily; Hammett, Felix; Kronberga, Madara; Khawgali, Mohamed; Bonner, Clare; Saab, Ala; Balbola, Mohamed; Saha, Arin
Abstract: Background: The World Health Organisation declared a global pandemic on the 11 th March 2020 regarding the COVID-19 infection. This has had a dramatic impact on both acute and elective hospital services that will take a considerable time to recover from. Initial emergency intercollegiate surgical guidance released in March 2020 raised concern regarding laparoscopic surgery and advised to pursue alternative non-surgical or radiological treatment options for the safety of patients and theatre teams. The aim of this study was to assess the safety of emergency laparoscopic cholecystectomy (ELC) for patients presenting to our centre with acute gallstone pathology during the pandemic. Methods: Retrospective analysis of all cholecystectomies undertaken in the department during the first year of the pandemic from 11 th March 2020 to 11 th March 2021. This period encapsulated two recognised peaks of the pandemic in the United Kingdom. Demographic data, elective/emergency, operative time, postop ITU admissions due to COVID and COVID related mortality was collected. Operative numbers and times were compared with historical data (HD) from the previous five years over the same time frame. Results: 399 laparoscopic cholecystectomies were performed during the first year of the pandemic which was less than the previous five-year average of 570 cholecystectomies per annum (30% reduction). 247 (61.9%) were performed as an emergency on patients presenting with acute gallstone pathology compared to 35% (HD) performed acutely on average historically. Average age was 56 yrs (16-88 range). Average operative time for ELC during the pandemic was 69 minutes compared to 78 minutes HD (NS). No patients were admitted to ITU with post-operative Covid infections and there were no 30 day post-operative deaths. Conclusions: We performed more ELC's in the first year of the pandemic compared to the previous five-year average as we were conscious of the inevitable long waiting lists, we would certainly be faced with in the coming months. The Covid-19 pandemic was a global healthcare crisis and one the NHS had never encountered before. At the time there was no high-quality evidence on the safety of laparoscopy on patients presenting acutely. This study adds to the growing body of evidence that with consistent preoperative testing, PPE and appropriate patient flow pathways that emergency laparoscopic cholecystectomies are safe to perform in the current climate.